Rare Functional Variants in Complement Genes and Anti-FH Autoantibodies-Associated aHUS - Valoti, Elisabetta; Alberti, Marta; Iatropoulos, Paraskevas; Piras, Rossella; Mele, Caterina; Breno, Matteo; Cremaschi, Alessandra; Bresin, Elena; Donadelli, Roberta; Alizzi, Silvia; Amoroso, Antonio; Benigni, Ariela; et al. (Frontiers in Immunology, 2019)
Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by microangiopathic hemolytic anemia, thrombocytopenia and renal failure. It is caused by genetic or acquired defects of the complement alternative pathway. Factor H autoantibodies (anti-FHs) have been reported in 10% of aHUS patients and are associated with the deficiency of factor H-related 1 (FHR1). However, FHR1 deficiency is not enough to cause aHUS, since it is also present in about 5% of Caucasian healthy subjects. In this study we evaluated the prevalence of genetic variants in CFH, CD46, CFI, CFB, C3 and THBD in aHUS patients with anti-FHs, using healthy subjects with FHR1 deficiency, here defined “supercontrols”, as a reference group. “Supercontrols” are more informative than general population because they share at least one risk factor (FHR1 deficiency) with aHUS patients. We analyzed anti-FHs in 305 patients and 30 were positive. The large majority were children (median age: 7.7 [IQR, 6.6-9.9] years) and 83% lacked FHR1 (n =25, cases) due to the homozygous CFHR3-CFHR1 deletion (n =20), or the compound heterozygous CFHR3-CFHR1 and CFHR1-CFHR4 deletions (n =4), or the heterozygous CFHR3-CFHR1 deletion combined with a frameshift mutation in CFHR1 that generates a premature stop codon (n =1). Of the 960 healthy adult subjects 48 had the FHR1 deficiency (“supercontrols”). Rare likely pathogenetic variants in CFH, THBD and C3 were found in 24% of cases (n =6) compared to 2.1% of the “supercontrols” (P-value =0.005). We also found that the CFH H3 and the CD46GGAAC haplotypes are not associated with anti-FHs aHUS, whereas these haplotypes are enriched in aHUS patients without anti-FHs, which highlights the differences in the genetic basis of the two forms of the disease. Finally, we confirm that common infections are environmental factors that contribute to the development of anti-FHs aHUS in genetically predisposed individuals, which fits with the sharp peak of incidence during scholar-age. Further studies are needed to fully elucidate the complex genetic and environmental factors underlying anti-FHs aHUS and to establish whether the combination of anti-FHs with likely pathogenetic variants or other risk factors influences disease outcome and response to therapies.